Potential invivo antidiabetic activity of "aavari kudineerformulation" (akf) in normal and streptozotocin Induced type-ii diabetic rats - PRAKASH YOGANANDAM G; GOPAL V; THANKA J (International Journal of Pharma and Bio Sciences, 2016)
The present study demonstrates that “Aavarai Kudineer formulation” (AKF) exhibits promising antidiabetic activity and help to maintain good glycemic and metabolic control. The herbal formulation, AKF elicit hypo-glycaemic and antidiabetic effects in both normal and Streptozotocin (STZ) induced type- II hyperglycemic rats. The herbal formulation under acute toxicity studies shows, it is non toxic upto 2000mg/kg/BW. It is possible that the herbal formulation may act through both, pancreatic and extra-pancreatic mechanism(s). This Aavarai Kudineer formulation elicited a significant antidiabetic effect in Streptozotocin induced diabetic rats as reflected by its ability to inhibit lipid peroxidation and to elevate the enzymatic antioxidants in pancreatic tissue. This extract showed improvement in parameters like body weight, food consumption, organ weight and biochemical parameters and might be of great valuable in diabetic treatment. The histopathological studies during 28 days long term treatment have shown to ameliorate the Streptozotocin induced histological damage of Islets of Langerhans. Moreover the inhibitory effects on biochemical and histological parameters induced by herbal formulation at a dose of 500mg/kg were almost comparable to that of standard drug, Glibenclamide (5mg/kg).